Flame‐Assisted Synthesis of O‐Coordinated Single‐Atom Catalysts for Efficient Electrocatalytic Oxygen Reduction and Hydrogen Evolution Reaction. Issue 1 (2nd December 2021) - Li, Jinze; Li, Hao; Xie, Wenfu; Li, Shijin; Song, Yuke; Fan, Kui; Lee, Jin Yong; Shao, Mingfei
Abstract: Single‐atom catalysts (SACs) exhibit intriguing performance in electrocatalysis owing to their maximized atom utilizations and unique electronic structures, but effective anchoring metal atoms with defined coordination structure on hierarchical integrated electrode remain a challenge. Herein, a fast and facial flame‐assisted strategy is developed to construct oxygen‐coordinated SACs on integrated carbon nanotube (CNT) arrays with promising applications in electrocatalysis. Density functional theory calculations show that oxygen in carbon substrate imparts homogeneous sites for the efficient anchoring of metal atoms, thereby enabling SACs to disperse uniformly and firmly and thus bringing optimized activities. Moreover, the integrated CNT array with abundant oxygen‐containing groups is constructed and has been used as an efficient matrix for anchoring metal atoms (CNT‐O@M) via a flame‐assisted method. The as‐prepared CNT‐O@M (M = Co and Pt as typical examples) shows excellent activities in electrocatalytic oxygen reduction reaction and hydrogen evolution reaction with utilization of active site as high as 75.7%, which is superior to the reported SACs. Particularly, the performance of CNT‐O@M can maintain stably under various harsh conditions, showing a promising prospect in the long‐time applications. The methodology and concept proposed in this work could be extended to the synthesis of a variety of integrated SACs for efficient electrocatalysis. Abstract : Well‐defined O‐coordinated single‐atom catalysts on integrated carbon nanotube arrays (CNT‐O@M, M = Co, Pt) are synthesized by facial flame‐assisted method, which shows excellent activities for ORR and HER with utilization of active site as high as 75.7%. The methodology and concept proposed in this work could be extended to the synthesis of a variety of integrated single‐atom catalysts for efficient electrocatalysis.